1989
DOI: 10.1172/jci114186
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the cytokines interleukin 6, tumor necrosis factor-alpha, and interleukin 1-beta secreted by acute myelogenous leukemia blasts in autocrine and paracrine leukemia growth control.

Abstract: Autonomous in vitro growth of myeloid leukemic colony-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(75 citation statements)
references
References 41 publications
4
69
1
1
Order By: Relevance
“…Of these inhibitors, TNF-a (33, 34) and H-ferritin (35) are reported to be released from LC, especially from AMLcells. However, the present data showed that the TNF-a levels in all the LC-CMstudied were minimal or below the detectable limit, agreeing with a report of Griffin and colleagues (36), but contrasting with other reports in which LCfrom the majority of AMLpatients were shown to release considerable amounts of TNF-a (33,34). Causes of such discrepancy are not clear, but may be due mainly to differences in the cell source and the method of preparation of LC-CM.…”
Section: Effect Of Viable Lc and Lc-cmon Km-101 Cellssupporting
confidence: 83%
“…Of these inhibitors, TNF-a (33, 34) and H-ferritin (35) are reported to be released from LC, especially from AMLcells. However, the present data showed that the TNF-a levels in all the LC-CMstudied were minimal or below the detectable limit, agreeing with a report of Griffin and colleagues (36), but contrasting with other reports in which LCfrom the majority of AMLpatients were shown to release considerable amounts of TNF-a (33,34). Causes of such discrepancy are not clear, but may be due mainly to differences in the cell source and the method of preparation of LC-CM.…”
Section: Effect Of Viable Lc and Lc-cmon Km-101 Cellssupporting
confidence: 83%
“…43 Sensitivity of blast cells to GM-CSF in vitro appeared to be inversely related with early treatment response which may be explained by the autocrine production of hematopoietic growth factors in AML blasts. [44][45][46][47] These results were confirmed by Tsuzuki and coworkers, 48 showing that patients whose leukemic cells had a positive proliferative response to growth factors had a poorer outcome.…”
Section: Introductionmentioning
confidence: 79%
“…Moreover, TNFa acts on the more mature hematopoietic cell compartment by inhibiting the development of committed myeloid progenitors (Murase et al, 1987), and interfering with both erythroid and megacaryocyte precursor terminal differentiation (De Maria et al, 1999). Consistent with these findings, TNFa overproduction has been implicated in hematopoietic failure related to diverse pathological situations, such as severe infections, cancers, and hematopoetic disorders, including myelodysplasia (MDS) (Kitagawa et al, 1997), acute myeloid leukemia (AML) (Oster et al, 1989), and aplastic anemia (Young, 2000).…”
Section: Introductionmentioning
confidence: 87%